Toward Improving Practices for Submission of Diagnostic Tissue Blocks for National Cancer Institute Clinical Trials. Issue 2 (15th October 2019) - Makhlouf, Hala; Watson, Mark A; Lankes, Heather A; Weil, Carol; Dickler, Maura; Birrer, Michael; Moskaluk, Christopher; Ramirez, Nilsa C; Okby, Nader; Alonsozana, Edgar; Barnes, Mark; Goldman, Edward B; et al.
Abstract: Objectives: The National Cancer Institute (NCI) National Clinical Trials Network performs phase II and III clinical trials, which increasingly rely on the submission of diagnostic formalin-fixed, paraffin-embedded tissue blocks for biomarker assessment. Simultaneously, advances in precision oncology require that clinical centers maintain diagnostic specimens for ancillary, standard-of-care diagnostics. This has caused tissue blocks to become a limited resource for advancing the NCI clinical trial enterprise and the practice of modern molecular pathology. Methods: The NCI convened a 1-day workshop of multidisciplined experts to discuss barriers and strategic solutions to facilitate diagnostic block submission for clinical trial science, from the perspective of patient advocates, legal experts, pathologists, and clinical oncologists. Results: The expert views and opinions were carefully noted and reported. Conclusions: Recommendations were proposed to reduce institutional barriers and to assist organizations in developing clear policies regarding diagnostic block submission for clinical trials.